Lymphatic Endothelial Cells Produce M‐CSF, Causing Massive Bone Loss in Mice. (31st January 2017) - Wang, Wensheng; Wang, Hua; Zhou, Xichao; Li, Xing; Sun, Wen; Dellinger, Michael; Boyce, Brendan F; Xing, Lianping
ABSTRACT: Gorham‐Stout disease (GSD) is a rare bone disorder characterized by aggressive osteolysis associated with lymphatic vessel invasion within bone marrow cavities. The etiology of GSD is not known, and there is no effective therapy or animal model for the disease. Here, we investigated if lymphatic endothelial cells (LECs) affect osteoclasts (OCs) to cause a GSD osteolytic phenotype in mice. We examined the effect of a mouse LEC line on osteoclastogenesis in co‐cultures. LECs significantly increased receptor activator of NF‐κB ligand (RANKL)‐mediated OC formation and bone resorption. LECs expressed high levels of macrophage colony‐stimulating factor (M‐CSF), but not RANKL, interleukin‐6 (IL‐6), and tumor necrosis factor (TNF). LEC‐mediated OC formation and bone resorption were blocked by an M‐CSF neutralizing antibody or Ki20227, an inhibitor of the M‐CSF receptor, c‐Fms. We injected LECs into the tibias of wild‐type (WT) mice and observed massive osteolysis on X‐ray and micro‐CT scans. Histology showed that LEC‐injected tibias had significant trabecular and cortical bone loss and increased OC numbers. M‐CSF protein levels were significantly higher in serum and bone marrow plasma of mice given intra‐tibial LEC injections. Immunofluorescence staining showed extensive replacement of bone and marrow by podoplanin+ LECs. Treatment of LEC‐injected mice with Ki20227 significantly decreased tibial bone destruction. In addition, lymphatic vessels in a GSD bone sample were stained positively for M‐CSF. Thus, LECs cause bone destruction in vivo in mice by secreting M‐CSF, which promotes OC formation and activation. Blocking M‐CSF signaling may represent a new therapeutic approach for treatment of patients with GSD. Furthermore, tibial injection of LECs is a useful mouse model to study GSD. © 2017 American Society for Bone and Mineral Research.